STATE REGULATION OF THE ECONOMY WITH THE USE OF MULTILATERAL DEVELOPMENT BANKS ON THE EXAMPLE OF THE ASIAN-PACIFIC REGION - S. Matveevskii (Вестник университета)
The author showed, that financing and implementation of the projects of the Asian Development Bank, ensures state regulation of the economy of the countries of theAsia-Pacific region. Examples of concrete projects have given, sources of their financing, including budgetary funds have revealed. The author presented both financial and other results of the activities of the Asian Development Bank, allowing quantitative and qualitative assessment of both the impact of project implementation and the results of state regulation of the economy of the countries concerned. The experience of the Asian Development Bank can be using in Russia by such development institutions as Vnesheconombank, the Industrial Development Fund. The author suggested using bonds to increase the financing of Russian development institutions.